Hand, Foot And Mouth Disease: Are We Closer To Finding A Drug Or Vaccine? - Ahmad Mahfuz, Gazali (Social Health Analytics Sdn Bhd, 2022)
The increase in HFMD since April 2022 has been expected, because of the loosening of social restrictions and the opening of schools, kindergartens, and daycare centres.